FOREST ADVENTURE PARKS OF ROMANIA: NEW POSSIBILITIES TO DEVELOP THE HUMAN PHYSICAL CAPACITY - Béla József BALL; Iuliana BOROS-BALINT (Cluj University Press, 2019)
One of the primary goals of physical education is to improve the human physical capacity. The physical capacity is a dynamic potential of a person, which is composed by the level of motor abilities and motor skills acquired during life. School-based physical education plays an important role in the development of motor capacity, but it is by far not enough to achieve the goal of physical education. Purpose: The purpose of this study is to map the adventure parks of Romania and to examine (by reviewing the literature) the effect of climbing on the motor capacity of the participants. We would like to examine the most common obstacles in adventure parks and determine what physical abilities are needed to complete them. Case Presentation: In Romania, the first forest adventure park was built in 2006 and by now, their number has reached thirty. Their main characteristic is that the climbers, by relying on their own physical and mental abilities, try to cross obstacles of various difficulty, height and length. Conclusions: Moving activities provided by forest adventure parks have become easily available to more and more people. Climbing in adventure parks (and climbing in general) can be an excellent alternative to improving motor capacity, as it uses and develops the body in a versatile way. REZUMAT. Parcurile de aventură din România: noi posibilități pentru creșterea capacității motrice a omului. Unul dintre obiectivele primare ale educației fizice este dezvoltarea capacității motrice. Capacitatea motrică este un potențial dinamic, compus din nivelul de dezvoltare al calităților motrice și deprinderilor motrice. Educația fizică școlară are un rol important în dezvoltarea capacității motrice a elevilor, dar nu este suficientă pentru atingerea obiectivelor educației fizice. Scop: Scopul acestui studiu este prezentarea parcurilor de aventură din România și de a descrie (prin studiul literaturii de specialitate) efectul cățărării asupra capacității motrice. Am dori să descriem cele mai comune obstacole din parcurile de aventură și să determinăm acele calități și deprinderi motrice care se implică în cățărare. Rezultate: În România, primul parc de aventură forestier a fost construit în 2006 și până acum numărul lor a ajuns la treizeci. Principala lor caracteristică este că cățărătorii, bazându-se pe propriile abilități fizice și mentale, încearcă să traverseze obstacole de diferite dificultăți, înălțimi și lungimi. Concluzii: Activitățile motrice oferite de parcurile de aventură forestiere au devenit accesibile pentru tot mai mulți oameni. Cățărarea pe traseele cu obstacole (și cățărarea în general) poate fi o alternativă excelentă pentru îmbunătățirea capacității motrice. Cuvinte cheie: parc de aventură; cățărare; beneficii fizice; deprindere motrică.